Discovery of a novel Kv7 channel opener as a treatment for epilepsy. Issue 21 (1st November 2015) - Davoren, Jennifer E.; Claffey, Michelle M.; Snow, Sheri L.; Reese, Matthew R.; Arora, Gaurav; Butler, Christopher R.; Boscoe, Brian P.; Chenard, Lois; DeNinno, Shari L.; Drozda, Susan E.; Duplantier, Allen J.; Moine, Ludivine; et al.
Graphical abstract